THE EFFECTIVENESS OF FLIPPED LEARNING VIEWED FROM STUDENTS’ PERSPECTIVE (A Descriptive Qualitative Research on English for Nursing 2 Course at Universitas Harapan Bangsa) - Tri Pujiani (LINGUAMEDIA Journal, 2020)
English is necessary for nursing due to most of nurses’ job vacancy requires an expertise of English. However, not all nurses are able to communicate in English well. Considering the gap between the needs of English for nurses and the problems they faced in learning English itself, a course designed specifically based on the nurses needs of English in their daily work is required. Moreover, because the purpose of the course is being able to communicate in English, the learning method must be more practical rather than theory. Flipped learning is one of the learning methods that facilitates students-centered learning. This research was descriptive qualitative research aimed to evaluate the effectiveness of flipped learning implementation in English for Nursing course from the students’ perspective. One of the key factors in determining the success of a teaching method is the students’ engagement so that the students’ perspective toward the teaching method applied needs to be considered.  Based on the result of questionnaire and interview, most of the students gave positive responses toward the components of learning such as the materials, the learning activities, the assignment, the learning media, their engagement, and their motivation in learning. Thus, it can be concluded that from the students’ perspective flipped learning is effective to be applied in English for Nursing course.Keywords: Flipped learning, English for Nursing, Students’ perspective